﻿Les leçons singulières : Une sculpture urbaine - Lamarche, Lise (RACAR : Revue d'art canadienne / Canadian Art Review, 1991)
In 1990 and 1991, the city of Montreal commissioned a sculpture in two pieces, les Leçons singulières, from the artist Michel Goulet and erected it on two neighbouring sites: Place Roy and Parc Lafontaine. The city of Montreal “produced” the work through a contest modelling itself on the established procedures of the one-percent-programmes. It was the first of its kind to be organized by the City and the large action programme is still going on as of today. The local newspapers reviewed les Leçons singulières very negatively especially the piece occupying Place Roy arguing the disappearance of a parking lot and the poor quality of the surrounding buildings. It initiated a debate on the nature and the uses of public spaces and even involved the architects, the urban designers, the landscape architects and the municipal services, all of whom seemed to be acting as the actual “authors” of the litigated place. Even the users of Place Roy voiced their opposition in the newspapers and in the electronic media insisting mainly on the uselessness of the “chairs,” the formal disposition of the work which reduced it to some sort of installation rather than the expected vertical monolith. A careful analysis of the written press and the examination of diverse markings found on the site itself (some strange use of the area, graffiti, etc.) reveal also some individual reactions and private interests and possibly some understated political agenda. Besides being an innovative piece of public sculpture, les Leçons singulières remains an exemplary case study of art in the public space. This article analyzes the reception of the double piece in the media and examines how those different levels of intervention in public commissions tend to erase the artist as main author of the work.